Immune development of children born from Caesarean section - Zakiudin Munasir; Levina Chandra Khoe (Indonesian Nutrition Association, 2020)
Several studies results have shown that mode of delivery affects the health of children, and recent studies showed that elective cesarean section (CS) is associated with aberrant short-term immune responses in the newborn baby and an increased risk of developing immune disorders. This article focused on the effect and role of the C-section on the immune development in children. Begin at pregnancy, the infant's immune system is activated and develops years after birth. In this article we find that cesarean delivery mode will influence the offspring's immune system by disrupting the intestinal tract's bacterial colonization, different levels of birth adaptive stress, and altering gene expression epigenetic regulation. Some studies have found that gut microbiome composition plays a significant role in the development of immune system along with other factors such as diet/lifestyle, antibiotic use, formula feeding, vaccination with life vaccine, and pathogen exposure. In early life, disrupted colonization induced dysbiosis that was associated with lower Bifidobacteria and higher counts of C. difficile. These findings are related to infant immune disease and allergy. Dysbiosis following C-section has a huge effect of developing altered immune system, and this microbiome imbalance can be controlled by nutritional support such as maternal breast milk or the use of different combinations of prebiotics and probiotics (synbiotic) which could be beneficial for the immune and metabolic system.